Differential cytotoxicity but augmented IFN-γ secretion by NK cells after interaction with monocytes from humans, and those from wild type and myeloid specific COX-2 knockout mice - Tseng, Han-Ching; Arasteh, Aida; Kaur, Kawaljit; Kozlowska, Anna; Topchyan, Paytsar; Jewett, Anahid (Frontiers in Immunology, 2015)
The list of genes which augment NK cell function when knocked out in neighboring cells is increasing, and may point to the fundamental function of NK cells targeting cells with diminished capability to differentiate optimally since NK cells are able to target less differentiated cells, and aid in their differentiation. In this paper we aimed at understanding the effect of monocytes from targeted knockout of COX-2 in myeloid cells (Cox-2flox/flox;LysMCre/+) and from control littermates (Cox-2flox/flox;LysM+/+) on ex vivo function of NK cells. Furthermore, we compared the effect of monocytes treated with and without lipopolysaccharide (LPS) on NK cells from mice and humans. NK cells purified from Cox-2flox/flox;LysMCre/+ mice had heightened cytotoxic activity when compared to those obtained from control littermates. In addition, NK cells cultured with autologous Cox-2flox/flox;LysMCre/+ monocytes and DCs, mouse embryonic fibroblasts (MEFs) from global knock out COX-2, but not with knock out of COX-2 in T cells, had increased cytotoxic function as well as augmented IFN-γ secretion when compared to NK cells from control littermates cultured with monocytes. LPS inhibited NK cell cytotoxicity while increasing IFN-γ secretion when cultured in the presence of monocytes from either Cox-2flox/flox;LysMCre/+ or control littermates. In contrast to mice, NK cells from humans when cultured with monocytes lost cytotoxic function and gained ability to secrete large amounts of IFN-γ, a process which we had previously coined as “split anergy”. Similar to mice, LPS potentiated the loss of human NK cell cytotoxicity while increasing IFN-γ secretion in the presence of monocytes. Greater loss of cytotoxicity and larger secretion of IFN-γ in NK cells induced by gene knock out cells may be important for the greater need of these cells for differentiation.